Deepwater fish assemblages at Isla del Coco National Park and Las Gemelas Seamount, Costa Rica - Richard M. Starr; Kristen Green; Enric Sala (Revista de Biología Tropical, 2012)
The deepwater faunas of oceanic islands and seamounts of the Eastern Tropical Pacific are poorly known. From 11-22 September 2009 we conducted an exploration of the deepwater areas of the Isla del Coco Marine Conservation Area, Costa Rica and a nearby seamount using a manned submersible. The goal of the exploration was to characterize the habitats and biota, and conduct quantitative surveys of the deepwater portions of Isla del Coco National Park and Las Gemelas Seamount, located about 50km southwest of Isla del Coco. We completed a total of 22 submersible dives, spanning more than 80hr underwater, and collected a total of 36hr of video. We surveyed habitats from 50-402m and observed more than 45 species of fishes, some of which have not yet been described and are likely new to science. The diversity of fish species in deep water at Isla del Coco National Park was lower than the diversity of fishes in shallow water, and eight species groups accounted for more than 95% of the total fish biomass. The combined density of all fish species was higher at Las Gemelas Seamount (253 fishes/100m²) than at Isla del Coco National Park (138 fishes/100m²). The combined density of fishes in habitats comprised primarily of bedrock or large boulders outcrops was more than three times as high at Las Gemelas Seamount as it was at Isla del Coco National Park. This discrepancy was caused by the extremely high concentration of Anthiinae fishes in rocky habitats at Las Gemelas Seamount. Densities of fishes in the other habitats were similar between the two sites. Similarly, when estimates of fish density were plotted by slope categories the density was much greater on steep slopes, which were usually comprised of rock habitats. Also, the density of fishes was greatest on high rugosity habitats. Results of these submersible surveys indicate that seamounts in the tropical eastern Pacific Ocean may be an important source of biodiversity and that more quantitative surveys are needed to characterize the fauna of the region.